2014
DOI: 10.1016/j.neurobiolaging.2013.11.030
|View full text |Cite
|
Sign up to set email alerts
|

The apolipoprotein E epsilon 4 allele is associated with ventricular expansion rate and surface morphology in dementia and normal aging

Abstract: The apolipoprotein E epsilon 4 allele (ApoE-ε4) is the strongest known genetic risk factor for late onset Alzheimer’s disease. Expansion of the lateral ventricles occurs with normal aging, but dementia accelerates this process. Brain structure and function depend on ApoE genotype not just for AD patients but also in healthy elderly, and even in asymptomatic young individuals. Therefore, we hypothesized that the ApoE-ε4 allele is associated with altered patterns of longitudinal ventricular expansion, in dementi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
0
23
2
1
Order By: Relevance
“…Whereas studies overwhelmingly find that the APOE "4 genotype is associated with worse amyloid-b pathology, its effect on markers of neurodegeneration such as CSF tau, fludeoxyglucose PET, and structural MRI are less consistent. Studies have reported both an influence of the APOE "4 allele (Reiman et al, 1996;Galasko et al, 1998;Liu et al, 2010;Jagust et al, 2012;Hostage et al, 2013;Lehmann et al, 2013;Roussotte et al, 2014) and no effect (Soininen et al, 1995;Jack et al, 1998;Reiman et al, 1998;Sunderland et al, 2004;Drzezga et al, 2009;Fan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas studies overwhelmingly find that the APOE "4 genotype is associated with worse amyloid-b pathology, its effect on markers of neurodegeneration such as CSF tau, fludeoxyglucose PET, and structural MRI are less consistent. Studies have reported both an influence of the APOE "4 allele (Reiman et al, 1996;Galasko et al, 1998;Liu et al, 2010;Jagust et al, 2012;Hostage et al, 2013;Lehmann et al, 2013;Roussotte et al, 2014) and no effect (Soininen et al, 1995;Jack et al, 1998;Reiman et al, 1998;Sunderland et al, 2004;Drzezga et al, 2009;Fan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Structural neuroimaging patterns related to APOE ε4 in elderly individuals described grey matter atrophy in the medial temporal structures (Chen et al, 2007, Donix et al, 2010b, Hua et al, 2010, Risacher et al, 2010, Lu et al, 2011, Roussotte et al, 2014 such as the subiculum (Burggren et al, 2008, Suthana et al, 2010) and CA1 subfield (Kerchner et al, 2014) of the hippocampus (Donix et al, 2010a, Chiang et al, 2011, O'Dwyer et al, 2012, Taylor et al, 2014, although contrasting results were published as well (Jack et al, 1998, Du et al, 2006, Schuff et al, 2009, Taylor et al, 2014. Moreover, higher cortical betaamyloid deposition (Reiman et al, 2009, Morris et al, 2010, glucose hypometabolism in brain regions typically impaired in AD (Rimajova et al, 2008, Fouquet et al, 2014 and changes in brain function during an encoding memory task (Filippini et al, 2011) were previously described in elderly cognitive intact individuals carrying the APOE ε4 allele.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the concept of preclinical AD [ 5 ], which has now been validated in autopsy studies of non-demented elderly subjects with neuropathological evidence of AD [ 6 10 ], brain imaging studies [ 11 19 ], amyloid detection [ 20 ], and neuropsychological studies [ 21 , 22 ]. Surface-based subregional structure analysis may offer additional benefits [ 17 , 23 26 ], such as better visualization and increased statistical power, especially when detecting subtle genetic effects. As the paradigm in experimental therapeutics shifts toward earlier intervention and prevention, enrichment of treatment cohorts with APOE e4 carriers may improve diagnostic accuracy and may make it faster to evaluate treatments for preclinical AD [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%